Maximizing spectral efficiency under minimum satisfaction constraints on multiservice wireless networks - Francisco Rafael Marques Lima (2012)
Cellular networks are now a new player in the competitive market of data service provision mainly due to the technological advances of 3rd Generation (3G) and the upcoming 4th Generation (4G). Long Term Evolution (LTE) and LTE-Advanced are examples of systems that are capable of providing high data rates to the end user. The need of being connected anytime and anywhere and the appealing mobile devices/applications are strong indications that the mobile broadband market has potential for further worldwide increasing. This new scenario with sophisticated mobile terminals enables the quick popularization of new appealing data mobile applications. As a consequence, it is expected that the traffic on mobile networks will have a considerable increase in the next years. Therefore, the sustainable Quality of Service (QoS) provision of heterogeneous services appears as a challenging scenario for mobile network operators and industry in the near future. In order to deal with this challenging scenario, improvements in the core network have been done by means of an Internet Protocol (IP)-based packet-switched architecture. In the radio access network, the use of Orthogonal Frequency Division Multiple Access (OFDMA) and Single Carrier - Frequency Division Multiple Access (SC-FDMA) as the multiple access schemes of downlink and uplink of LTE system, respectively, and the addition of multiple antennas techniques have boosted the achieved data rates in the radio part of the networks. Another relevant functionality that is useful to deal with the challenges of next generation cellular networks is efficient Radio Resource Allocation (RRA). RRA algorithms interact with multiple access schemes and multiple antenna schemes and are responsible for the management of the scarce radio resources such as power, time slots, spatial channels and frequency chunks. In this context, we study in this thesis the use of RRA in cellular networks in order to improve the resource usage efficiency and guarantee the sustainable provision of multiple services. More specifically, we model this RRA problem as the optimization problem of maximizing the overall data rate subject to minimum satisfaction constraints per service. Along this thesis, we study this problem in different scenarios with different multiple access strategies and multiple antennas schemes. As main contributions we provide the characterization of optimal solutions, proposal of low-complexity heuristic solutions, performance evaluation by means of computational simulations and computational complexity analysis of the involved algorithms.